Profil Hematologi pada Anak dengan Suspek Covid-19 di RSD Idaman Banjarbaru Tahun 2020 – 2021 - Sarah Nur Azizah; Roselina Panghiyangani; Harapan Parlindungan Ringoringo; Edi Hartoyo; Rahmiati Rahmiati (Homeostasis, 2022)
Abstract: Corona virus disease (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 affects all age groups from neonates to the elderly. Haematological profile have been used as important diagnostic and prognostic indicators in COVID-19. The aim of this study is to determine the hematological parameters including erythrocytes, haemoglobin (Hb), hematocrit, Mantzer index (IM), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin Concentration (MCHC), leukocytes (type count: basophils, eosinophils, band neutrophils, segments neutrophil, lymphocytes, monocytes), platelets, and Neutrofil Limphocytes Ratio (NLR) in children with suspected COVID 19 at Idaman Hospital Banjarbaru 2020-2021. This study is done using descriptive retrospective method of the suspected COVID-19 pediatric patients. The data used on this study is medical records of the pediatric patients with suspected COVID-19 at Idaman Hospital Banjarbaru 2020-2021. The results showed that children with suspected COVID-19 had normal values of the hematological parameters including RBC 69.81%, Hb 69.8%, hematocrit 73.5%, MCV 67.92%, MCH 58.49%, MCHC 84.90%, leukocytes 67.92%, basophils 98.11%, platelets 69.81% and RNL 66.03%. The decrease in value occurred in the eosinophil parameter as much as 62.26%, bands neutrophils 88.6% and segment neutrophils 45.28%. An increase in the value occurred in the hematological parameters of lymphocytes as much as 41.5%, monocytes 49.05%, and Mantzer index 92.47%. Keywords: children, COVID-19, haematology profile Abstrak: Corona virus disease (COVID-19) merupakan penyakit menular yang diakibatkan Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 menyerang semua kelompok usia dari neonatus hingga lanjut usia. Parameter hematologi penting dalam mendiagnosis COVID-19 dan menilai prognosis pasien. Tujuan dilaksanakannya penelitian ini untuk mengetahui profil hematologi, meliputi eritrosit, hemoglobin (Hb), hematocrit, Indeks Mantzer (IM), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH), Mean Corpuscular Haemoglobin Concentration (MCHC), leukosit (hitung jenis: basofil, eosinofil, neutrofil batang, neutrofil segmen, limfosit, monosit), trombosit, dan Rasio Neutrofil Limfosit (RNL) pada anak dengan suspek COVID-19 di RSD Idaman Banjarbaru 2020-2021. Rancangan penelitian ini menggunakan metode penelitian deskriptif retrospektif, menggunakan data rekam medis pasien anak dengan suspek COVID-19 di RSD Idaman Banjarbaru Tahun 2020-2021. Hasil penelitian menunjukkan bahwa anak dengan suspek COVID – 19 lebih banyak memiliki nilai normal pada parameter hematologi RBC sebanyak 69,81%, Hb 69,8%, hematokrit 73,5%, MCV 67,92%, MCH 58,49%, MCHC 84,90%, leukosit 67,92%, basofil 98,11%, trombosit 69,81% dan RNL 66,03%. Penurunan nilai terjadi pada parameter eosinofil sebanyak 62,26%, neutrofil batang 88,6% dan neutrofil segmen 45,28%. Peningkatan nilai terjadi pada parameter hematologi limfosit sebanyak 41,5%, dan monosit 49,05% dan Indeks Mantzer sebanyak 92,47%. Kata-kata kunci: anak, COVID-19, profil hematologi